Meningkatkan Hasil Belajar Matematika Materi Penyajian Data Menggunakan Model Problem Based Learning (PBL) Pada Siswa Kelas V Di UPTD SDN 1 Kait-Kait Kabupaten Tanah Laut - Nor Latifah; Sunarno (CV. ITTC INDONESIA, 2023)
The problem in this study is that learning is one-way, there is no learning that can stimulate students to improve problem-solving skills, and learning is still not varied. The purpose of this research is to describe the activities of educators and students and to increase learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research (CAR). The type of data used is qualitative data in the form of observing the activities of educators and students during learning activities as well as quantitative data namely learning outcomes in the cognitive, affective and psychomotor domains. These results show that the activity of educators in cycle I reached 17